Building Employee Performance Based on Compensation and Work Training With Variables of Work Satisfaction (Performance Analysis of PT. Harapan Abadi Employees) - Muhammad Irfan Rahadian; I Ketut R Sudiarditha; Ari Saptono (Journal of Accounting and Finance Management, 2020)
This study aims to analyze compensation and training on employee performance through satisfaction variables. This research uses a quantitative method using the SEM Lisrel 8.8 Program analysis tool. The number of respondents was 105 employees of PT. Sumber Harapan Abadi (DataPrint). The sampling technique in this study was purposive non-probability sampling using the Isaac and Michael method approach. The novelty in this study is the positive effect of compensation and job training on employee performance through employee job satisfaction. The results of the study stated: 1) there was a positive and significant effect of compensation on job satisfaction. 2) there is a significant positive effect of training on job satisfaction 3) there is a positive and significant effect of the effect of compensation on performance.4) a positive and significant effect of training on performance.5) there is a positive and significant effect of job satisfaction on performance 6) there is a positive and significant effect of training on performance. 7) the positive and significant influence of the effect of training on performance through job satisfaction.